Stasiun Cuaca Mini Portable Pengukur Komponen Cuaca untuk Menunjang Kegiatan Agribisnis - Wendy Triadji Nugroho (Jurnal Ilmiah Inovasi, 2017)
Wind speed, rainfall, solar radiation, temperature, relative humidity, and soil acidity are the components affecting climate, whereas climate has a major influence in agriculture. This study aims to develop measurement technology of several components which give influence to the climate, such as wind speed, rainfall, solar radiation, temperature, relative humidity, and soil acidity. Those sensors are integrated in a prototype called the Portable Mini Weather Station. This research is a Competitive Grant Program funded by Kemristekdikti for two years. The research method applied is the design and manufacture of prototype as well as its performance test in the first year. While in the second year is an improving this model by adding solar cells and dry battery, so that, this device can recharge or generate power independently to fulfill its operational needs. Besides, there is the addition of logger data along with module modification that translates inputs from several sensors to the LCD. Then, the weather information will be stored into the logger data.Keywords - Portable Mini Weather Station, components affecting climate, performance test, prototype, logger data